Discontinuous Arabic frozen expressions modelization and implementation - Asmaa Kourtin; Asmaa Amzali; Mohammed Mourchid; Samir Mbarki (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Frozen expressions hold significant importance in the field of natural language processing, attracting considerable attention from researchers across various languages in recent years. The Arabic language, in particular, boasts a wealth of frozen expressions inherited from the pre-Islamic and early Islamic periods, with persistent usage to the present day. This linguistic richness has motivated researchers to systematically collect, classify, and elucidate these expressions. Various classifications have emerged, addressing aspects such as continuity, discontinuity, allowance for variations, and restriction from variations. Our aim is to produce lexicon-grammar tables of discontinuous Arabic frozen expressions and implement them. Our approach involves the meticulous collection and study of these expressions, followed by the transformation of their lexicon-grammar tables into dictionaries and syntactic grammars within the NooJ platform. This methodology allows us to recognize and annotate these expressions in texts and corpora, even when they exhibit discontinuity. Such recognition has the potential to address several challenges in automatic natural language processing, including the area of automatic translation.